Dosis de gallinaza y sus efectos sobre las características agronómicas y rendimiento de Solanum Lycopersicum M. "tomate regional", Zungarococha - Loreto. 2019 - Mananita Flores, Beberly (2021)
The research work "Dose of hen and its effects on the agronomic characteristics and yield of Solanum Lycopersicum M. "regional tomato", Zungarococha- Loreto. 2019", was developed in the Workshop of Teaching and Research of Horticultural Plants of the Faculty of Agronomy-UNAP, whose geographical coordinates are: Latitude South 03o 46 x 13.2; West Length 73o 22 x 10.4; Elevation: 126 meters above sea level. The type of research was experimental explanatory, prospective, transversal with an independent variable (dose of hen) and eight dependent variables (plant height, plant extension, fruit length, fruit diameter, fruit/plant number, fruit weight, fruit/plant weight and fruit/ha weight. The overall objective was to determine the influence of hen doses on the agronomic characteristics and yield of Solanum Lycopersicum M. "regional tomato". The experimental design used was Completely Random Block Design (DBCA), with four treatments and four repetitions. The treatments studied were: T1 (0 t of hen/ha, T2 (30 t of hen/ha), T3 (40 t of hen/ha and T4 (50 t of hen/ha. The following conclusions were reached: T1 (0 t of hen/ha) presented the best average values of height and extent of the plant, with 115 and 90 cm respectively; in relation to the length of the fruit, the average values did not differ significantly whose values were 5 cm in treatments T4 and T3 and 4 cm in T2 and T1; with respect to the diameter of the fruit, the T3 and T4 treatments had the best average values, with 6.05 and 5.23 cm respectively; also, the highest number of fruits/plant, with 15 fruits each; in relation to fruit weight, fruit/plant weight and fruit/ha weight, the T3 treatment (40 t of hen/ha) presented the best averages with 53 g; 1,525 g. and 36,600 kg/ha respectively, significantly outperfiding the other Treatments studied; I also generate a net balance of S/.60,770.00.